2019
DOI: 10.5492/wjccm.v8.i5.59
|View full text |Cite
|
Sign up to set email alerts
|

Successfully non-surgical management of flail chest as first manifestation of multiple myeloma: A case report

Abstract: Pneumonia and acute respiratory distress syndrome are common and important causes of respiratory failure in the intensive care unit with a significant impact on morbidity, mortality and health care utilization despite early antimicrobial therapy and lung protective mechanical ventilation. Both clinical entities are characterized by acute pulmonary inflammation in response to direct or indirect lung injury. Adjunct anti-inflammatory treatment with corticosteroids is increasingly used, although the evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 97 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Hyperlactatemia usually occurs in inadequate tissue perfusion and oxygenation, and is common in Sars-CoV-2 infection, since hypoxia is the mainstay of severe COVID-19, also in older COVID-19 patients ( Foucher & Tubben, 2020 ; Bahl et al 2020 ). C-reactive protein level correlates to inflammation and its concentration is not affected by age, sex, and physical condition ( Chalmers et al 2019 ). CRP is also a well-known index of severe pulmonary infections, and CRP levels were found to positively correlate with disease severity in COVID-19 (X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperlactatemia usually occurs in inadequate tissue perfusion and oxygenation, and is common in Sars-CoV-2 infection, since hypoxia is the mainstay of severe COVID-19, also in older COVID-19 patients ( Foucher & Tubben, 2020 ; Bahl et al 2020 ). C-reactive protein level correlates to inflammation and its concentration is not affected by age, sex, and physical condition ( Chalmers et al 2019 ). CRP is also a well-known index of severe pulmonary infections, and CRP levels were found to positively correlate with disease severity in COVID-19 (X.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is also a well-known index of severe pulmonary infections, and CRP levels were found to positively correlate with disease severity in COVID-19 (X. Guan et al 2021 ; Huang et al 2020 ; Chen et al 2020 ; Jin et al 2020 ; WHO Coronavirus Disease (COVID-19) Dashboard 2021 ; Covino, De Matteis, et al 2020 ; Chalmers et al 2019 ; Wang 2020 ). These results confirmed that an elevated CRP could have a predictive role in patients ≥ 80 years with COVID-19 ( Covino, De Matteis, et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of CRP are not affected by factors such as age, sex, and physical condition, and correlate with the level of inflammation 46 . As such, this is an important index for the diagnosis and assessment of severe pulmonary infectious diseases 47,48 . In the early stage of COVID-19, CRP levels could reflect lung lesions and disease severity 49 as such levels correlate with the level of inflammation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein we detected a significant reduction in CRP in patients after two administrations of HeberFERON (see figure 3). An important finding as CRP is an key index for the diagnosis and assessment of severe pulmonary infectious diseases 50,51 . In the early stage of COVID-19, CRP levels could reflect lung lesions and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Complement-mediated tissue injury is elicited by an intense inflammatory loop secondary to C3a-and C5a-mediated recruitment and activation of neutrophils, monocytes, macrophages, lymphocytes, and platelets. Phagocytes in turn generate reactive oxygen species (ROS) and proteases, and neutrophils release neutrophil extracellular traps (NETs), which exacerbate tissue damage (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%